Salidroside‐Pretreated Mesenchymal Stem Cells Enhance Diabetic Wound Healing by Promoting Paracrine Function and Survival of Mesenchymal Stem Cells Under Hyperglycemia. (9th January 2019) - Ariyanti, Agnes Dwi; Zhang, Jianqi; Marcelina, Olivia; Nugrahaningrum, Dyah Ari; Wang, Guixue; Kasim, Vivi; Wu, Shourong
Abstract: Systemic abnormalities cause several complications in diabetes patients. Impaired wound healing is a serious complication that leads to severe foot ulcer and amputation. Mesenchymal stem cells (MSCs) have been considered a promising strategy for promoting wound healing due to their paracrine function. However, their poor survival after transplantation limits their therapeutic effect and applications. Salidroside, a glucopyranoside, has been reported to exert cytoprotective effects. Our previous study revealed that salidroside could promote the paracrine function of skeletal muscle cells. However, whether salidroside could improve MSCs survival under hyperglycemic condition and, subsequently, promote wound healing in diabetic model mice remains unknown. Here, we found that salidroside pretreatment effectively reversed the hyperglycemia‐induced suppression of the expression of crucial wound healing factors in MSCs, such as heme oxygenase‐1 (HO‐1), fibroblast growth factor 2 (FGF2), and hepatocyte growth factor (HGF). Salidroside pretreatment also suppressed the hyperglycemia‐induced intracellular reactive oxygen species (ROS) levels in MSCs, thereby lowering the apoptosis rate and enhancing MSCs survival rate. Furthermore, salidroside improved the MSCs migration potential that was impaired under hyperglycemia. in vivo experiments revealed that salidroside pretreatment prior to transplantation significantly enhanced the effect of MSCs in promoting wound closure in diabetic mice. Collectively, our results suggest that pretreatment with salidroside could be an effective strategy to enhance the survival rate and the therapeutic effect of MSCs. Thus, our article suggested a novel, potential MSC‐based strategy for diabetic wound healing.Stem Cells Translational Medicine 2019;8:404–414 Abstract : Salidroside could restore the expression of HO‐1, FGF2 and HGF in mesenchymal stem cells (MSCs) impaired by hyperglycemia. The restoration of these factors improves the survival rate and migration potential of MSCs, which subsequently enhanced their effect in promoting wound closure in diabetic mice. Thus, salidroside‐pretreated MSCs might be a potential therapeutic strategy for diabetic wound healing.